PENGARUH GAYA HIDUP HEDONISME, MATERIALISME DAN PENDAPATAN TERHADAP IMPULSE BUYING PADA ONLINE SHOP PRODUK FASHION PADA MASYARAKAT KOTA BANDA ACEH - Erlinda, Erlinda - (Jurnal Bisnis Digital, 2021)
In digital era, shopping is easy and fun. This phenomenon has encouraged impulsive buying behavior among inhabitant. Therefore this study aims to determine the influence of hedonism, materialism life style, and income on impulse buying behavior of Banda Aceh resident. The population of this research is the resident In Banda Aceh municipality, who has shopped online fashion products. Research sample, collected 96 respondents based on convenience sampling, namely samples that are easy to find and have shopped for online fashion products. The data processing method uses multiple linear regression. The results showed that partially, the materialism lifestyle and income had a significant effect on impulse buying, while the hedonistic lifestyle had no significant effect on impulse buying. Simultaneously, the hedonistic lifestyle, materialism and income have a significant effect on impulsive buying at online shop of fashion products for Banda Aceh municipality residents. The distinguishes with previous research is in digital era, there has been shifting behavior in impulsive buying, without having to become a hedonist life style.